2016
DOI: 10.1038/ncomms10502
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of single-crystalline III–V semiconductors on amorphous substrates

Abstract: The III–V compound semiconductors exhibit superb electronic and optoelectronic properties. Traditionally, closely lattice-matched epitaxial substrates have been required for the growth of high-quality single-crystal III–V thin films and patterned microstructures. To remove this materials constraint, here we introduce a growth mode that enables direct writing of single-crystalline III–V's on amorphous substrates, thus further expanding their utility for various applications. The process utilizes templated liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 36 publications
1
63
0
1
Order By: Relevance
“…In this case, NiAu would promote the pyrolysis of NH 3 at a relatively low growth temperature (790 C), which is helpful for direct growth of nanodevices on unusual substrates of low melting temperature. [30][31][32][33][34][35] While, the growth of nanowires ( Fig. 2(d)) would have similar mechanism with VLS, because the nanowires have a high aspect ratio of $100, which can not be realized by using normal SAG.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, NiAu would promote the pyrolysis of NH 3 at a relatively low growth temperature (790 C), which is helpful for direct growth of nanodevices on unusual substrates of low melting temperature. [30][31][32][33][34][35] While, the growth of nanowires ( Fig. 2(d)) would have similar mechanism with VLS, because the nanowires have a high aspect ratio of $100, which can not be realized by using normal SAG.…”
Section: Discussionmentioning
confidence: 99%
“…With this method, high purity compounds are obtained. It is also reported that they offer high values of mobility, life time and free mean path for the minority carriers [17]- [21]. …”
Section: Epitaxial Growth Techniquesmentioning
confidence: 96%
“…indeed, control over defects enables the development of solid-state devices with fine-tuned mechanical resilience, optical properties, and heat and electrical conductivity [5][6][7][8][9]. In atomic crystals, engineering structural defects is an experimental challenge for two reasons [10]: first, current visualization techniques at the atomic scale do not provide a high spatial or time resolution [11,12]; second, no current technique can control the density of defects in a systematic manner [13].…”
mentioning
confidence: 99%
“…Since the coarsening time of these crystallites diverges with size, structural defects appear and prevent the emergence of global order [3,4]. While the existence of these defects is a challenge when growing single crystals, it can also be an opportunity when engineering the properties of materials; indeed, control over defects enables the development of solid-state devices with fine-tuned mechanical resilience, optical properties, and heat and electrical conductivity [5][6][7][8][9]. In atomic crystals, engineering structural defects is an experimental challenge for two reasons [10]: first, current visualization techniques at the atomic scale do not provide a high spatial or time resolution [11,12]; second, no current technique can control the density of defects in a systematic manner [13].…”
mentioning
confidence: 99%